LEVEL OF KNOWLEDGE REGARDING SUBSTANCE USE AND ITS ILL EFFECTS AMONG ADOLESCENT BOYS - U. Bhanupriya (Indian Journal of Psychiatric Nursing)
The study was aimed to assess the level of knowledge regarding substance use and its effects among adolescent boys at Z.P.H Schools at Guntur, Andhra Pradesh. A descriptive survey design was adopted and 60 adolescent boys were selected by simple random sampling technique. Data was collected by using self administered questionnaire regarding substance abuse. The study results showed that 90% of adolescent boys had average level of knowledge, 10% of adolescent boys had good level of knowledge where as none of them had poor knowledge with mean score of 25.1 + 4.95.